Are systemic prophylactic antibiotics necessary for burns? - Timmons, M. J. (Royal College of Surgeons of England, 1983)
Systemic prophylactic antibiotics to prevent Streptococcus pyogenes infections in newly burnt patients have been recommended for many years. However, a review of patients admitted to one Regional Burns Centre shows only a small percentage develop such infections, even if no systemic prophylaxis is used. Other Centres have reported similar results. Possible uses of systemic prophylactic antibiotics in patients with burns are reviewed. It is suggested that these antibiotics are restricted to a small minority of patients to prevent peri-operative septicaemia and gas-gangrene.